Oral Cellular Neurothekeoma - Nader Emami; Faisal Zawawi; Rania Ywakim; Ayoub Nahal; Sam J. Daniel (Case Reports in Otolaryngology)
Cellular neurothekeoma is known as a cutaneous tumor with uncertain histogenesis. Very little involvement of mucosal membrane has been reported in the literature so far. This is a case report of an intraoral lesion in a 15-years-old girl. Histopathologic evaluation showed a tumor-consists of spindle to epitheloid cells forming micronodules in a concentric whorled shape pattern. Tumor cells were positive for CD63, vimentin, and NKI-C3. Total excision was performed and no recurrence happened after 16-month followup.